Chemical Composition of the Essential Oil of Withania coagulans - BAKHTAWAR, SHAHNAZ; MUGHAL, TAHIRA; NAEEM*, ISMAT (Asian Journal of Chemistry, 2009)
The present research reports the chemical composition of the essential oil of Withania coagulans extracted by steam distillation and analyzed by GC-MS. The chromatographic analysis of this essential oil showed 20 compounds, representing 90.80 % of the total oil constituents. The oil contains a complex mixture consisting of sesquiterpenes, esters, acids, alkanes and aldehyde. It was dominated by sesquiterpenes (54 %) and esters (21.50 %) while alkanes, acids and aldehydes were only present in small percentage (9.11, 5.5 and 0.32 %, respectively). Thus carophyllene is present with highest percentage and allene is present with lowest percentage.